Technological imagination in the green and digital transition - Arbizzani, Eugenio (Urban book series, ISSN 2365-7588, 2023)
This open access book addresses the pressing need for sustainability in urban development and the use of technology, with cities to serve as the main stage for strategies that seek to meet the targets and the cross-sector priorities indicated in the EU’s Next Generation program, all in pursuit of a solid recovery on the part of the European economy, along lines of ecological transition, digitalization, competitiveness, training, and inclusion to overcome social, territorial, and gender differences. The international study encounter is meant to promote visions shared by architectural technology and other disciplines, which, though they may appear to differ, are closely interconnected, with the aim of achieving an open, interdisciplinary integration capable of proposing concrete projects regarding topics held to be of strategic importance to the future of the built environment. These are identified to draw up evolving scenarios of architecture and cities suited to reflection, at various levels, on innovative models of process and product.
Keywords: City planning : Technological innovations; Sustainable development; Electronic books